2022
DOI: 10.3390/polym14020349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrospinning Parameter Adjustment on the Mechanical Behavior of Poly-ε-caprolactone Vascular Scaffolds

Abstract: Electrospinning is a perspective method widely suggested for use in bioengineering applications, but the variability in currently available data and equipment necessitates additional research to ascertain the desirable methodology. In this study, we aimed to describe the effects of electrospinning technique alterations on the structural and mechanical properties of (1,7)-polyoxepan-2-one (poly-ε-caprolactone, PCL) scaffolds, such as circumferential and longitudinal stress/strain curves, in comparison with corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Thus, anisotropic uneven constructs have potential applications for the repair of organs with an anisotropic structure, such as the esophagus [18]. Ultrafine filament with a uniform fiber diameter is an important prerequisite for the effective mechanical properties of fiber membranes [19]. During the stretching process of the e-spun film, we found that it is more likely to break in areas where the material is thinner or of poorer quality.…”
Section: Resultsmentioning
confidence: 83%
“…Thus, anisotropic uneven constructs have potential applications for the repair of organs with an anisotropic structure, such as the esophagus [18]. Ultrafine filament with a uniform fiber diameter is an important prerequisite for the effective mechanical properties of fiber membranes [19]. During the stretching process of the e-spun film, we found that it is more likely to break in areas where the material is thinner or of poorer quality.…”
Section: Resultsmentioning
confidence: 83%
“…36 It is a relatively simple and efficient means of preparing nanofiber film materials, 37,38 which can control the surface morphology of the fiber films by simply adjusting the spinning parameters. 39,40 The fiber films prepared by electrospinning have high specific surface area and porosity, and the high porosity provides a great channel for medium transfer between the fibers in electrospinning, which accelerates the transfer and the high sensitivity. It is more favorable for more functional molecules to be distributed on the fiber surface, increasing the area of action.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning as a multifunctional technology opens a new window for smart fibers, which has attracted a lot of attention in the recent decades due to the simple method of producing micro- or even subnanometer fibers with excellent mechanical properties and especially flexibility . It is a relatively simple and efficient means of preparing nanofiber film materials, , which can control the surface morphology of the fiber films by simply adjusting the spinning parameters. , The fiber films prepared by electrospinning have high specific surface area and porosity, and the high porosity provides a great channel for medium transfer between the fibers in electrospinning, which accelerates the transfer and the high sensitivity. It is more favorable for more functional molecules to be distributed on the fiber surface, increasing the area of action. , More importantly, there have been few studies on the preparation of spiropyran-based photoresponsive materials using electrospinning technology.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the electrospinning technique can be particularly useful, since it allows the production of micro-nanostructured membranes with interconnected fibers recalling the extracellular matrix (ECM) architecture. The simplest set-up consists of the production of nanofibers by extruding a polymeric solution under an electric field. This allows obtaining three-dimensional (3D) nanofibrous mats, with different characteristics depending on the polymers chosen, as well as on process and environmental parameters ( i.e. , the applied voltage, the flow rate, the distance between the needle and the collector, the temperature, or the humidity). The nanofibrous meshes can be easily functionalized with bioactive cues, whose release can be regulated through the specific surface area, porosity, and fiber diameter, further promoting the structural and functional recovery of the injured site. …”
Section: Introductionmentioning
confidence: 99%
“…, the applied voltage, the flow rate, the distance between the needle and the collector, the temperature, or the humidity). 15 17 The nanofibrous meshes can be easily functionalized with bioactive cues, whose release can be regulated through the specific surface area, porosity, and fiber diameter, further promoting the structural and functional recovery of the injured site. 18 20 …”
Section: Introductionmentioning
confidence: 99%